2022
DOI: 10.3390/ijerph19159218
|View full text |Cite
|
Sign up to set email alerts
|

Profiling Police Forces against Stress: Risk and Protective Factors for Post-Traumatic Stress Disorder and Burnout in Police Officers

Abstract: Police officers are frequently exposed to highly stressful situations at work and have an increased risk to develop symptoms of post-traumatic stress disorder (PTSD) and burnout (BO). It is currently not well understood which officers are most at risk to develop these disorders. The aim of this study was to determine which coping strategies and personality traits could act as protective or risk factors in relation to PTSD and BO. The second aim, in the interest of designating preventive and therapeutical measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 147 publications
0
2
0
1
Order By: Relevance
“…The higher prevalence of younger individuals might imply a certain level of resilience among this age group in dealing with the stresses associated with police work. 11 Furthermore, police personnel may exhibit low levels of depressive and anxious symptoms due to their coping strategies and mental preparedness, but still experience heightened stress as a result of the chronic exposure to work-related stressors, as suggested by Arnetz et al, and Anders et al 12,13 This could explain why participants reported lower levels of depression and anxiety but moderate stress levels, as the latter may reflect the cumulative impact of ongoing occupational stressors.…”
Section: Discussionmentioning
confidence: 96%
“…The higher prevalence of younger individuals might imply a certain level of resilience among this age group in dealing with the stresses associated with police work. 11 Furthermore, police personnel may exhibit low levels of depressive and anxious symptoms due to their coping strategies and mental preparedness, but still experience heightened stress as a result of the chronic exposure to work-related stressors, as suggested by Arnetz et al, and Anders et al 12,13 This could explain why participants reported lower levels of depression and anxiety but moderate stress levels, as the latter may reflect the cumulative impact of ongoing occupational stressors.…”
Section: Discussionmentioning
confidence: 96%
“…Third, in this study, only the relationship between one contextual variable (i.e., social support) and PTSD was analyzed. However, several studies [29,70,86] have highlighted the importance of individual variables (e.g., personality traits and resilience) in explaining this syndrome. In this context, it is essential to emphasize that the COR seeks to better understand how psychological stress can be triggered and the degree to which resilience can be retained [17].…”
Section: Discussionmentioning
confidence: 99%
“…The police profession in society, increased social responsibility for the results, submission to certain requirements and the development of a set of personal qualities and legal consciousness limit the possible discussion of mental health problems and support in this organizational environment [9].…”
Section: Introductionmentioning
confidence: 99%